A stage-specific cell-manipulation platform for inducing endothelialization on demand. Issue 3 (21st November 2019) - Zhao, Qilong; Wang, Juan; Wang, Yunlong; Cui, Huanqing; Du, Xuemin
Abstract: Endothelialization is of great significance for vascular remodeling, as well as for the success of implanted vascular grafts/stents in cardiovascular disease treatment. However, desirable endothelialization on synthetic biomaterials remains greatly challenging owing to extreme difficulty in offering dynamic guidance on endothelial cell (EC) functions resembling the native extracellular matrix-mediated effects. Here, we demonstrate a bilayer platform with near-infrared-triggered transformable topographies, which can alter the geometries and functions of human ECs by tunable topographical cues in a remote-controlled manner, yet cause no damage to the cell viability. The migration and the adhesion/spreading of human ECs are respectively promoted by the temporary anisotropic and permanent isotropic topographies of the platform in turn, which appropriately meet the requirements of stage-specific EC manipulation for endothelialization. In addition to the potential of promoting the development of a new generation of vascular grafts/stents enabling rapid endothelialization, this stage-specific cell-manipulation platform also holds promise in various biomedical fields, since the needs for stepwise control over different cell functions are common in wound healing and various tissue-regeneration processes.